IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI DESA BAGJASARI KECAMATAN CIKIJING KABUPATEN MAJALENGKA - Amiruddin Setiawan; Syifa Aulia (Jurnal Ilmu Administrasi CENDEKIA, 2021)
ABSTRACTPoverty alleviation is a problem that must be immediately addressed by the government to immediately resolve and break the chain of causes. Poverty alleviation is currently still materially oriented so that sustainability is highly dependent on the availability of the budget and the government's commitment. One of the policy steps taken by the government to eradicate it is the Program Keluarga Harapan. With the implementation of Program Keluarga Harapan, it is hoped that it can improve the standard of socio-economic life, education, and public health, especially for the poor. The purpose of this study is to describe the implementation of Program Keluarga Harapan, find supporting and inhibiting factors and efforts to overcome them in Bagjasari Village, Cikijing District, Majalengka Regency. The research method used is descriptive research method with a qualitative approach. Data collection was used through observation and in-depth interviews. The results showed that the implementation of Program Keluarga Harapan in Bagjasari Village, Cikijing District, Majalengka Regency experienced several obstacles and had not been implemented properly. The socialization was carried out well, but the data collection process for Program Keluarga Harapan recipients was not comprehensive, there were still many who had not received Program Keluarga Harapan and the use of Program Keluarga Harapan funds by Keluarga Penerima Manfaat was often used outside the provisions. In the long term, it has not been able to change the mindset and behavior of Keluarga Penerima Manfaat significantly. Keywords: Policy Implementation, Family Hope Program.